Pengaruh Fasilitas Wisata Terhadap Kepuasan Pengunjung di Linggai Park, Tanjung Raya, Kab. Agam - Fadhil M. Adz-dzahaby; Adek Kurnia Fiza (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The research was carried out against the background, namely that there was a poor response from visitors to tourist facilities. The research purposes is to test the influence of tourist facilities on the sense of satisfaction of visitors at Linggai Park. This research type is quantitative descriptive research using an approach by causal associative. The population for this research is visitors who have visited Linggai Park, whose age is over 17 years. The research was conducted using a technique of purposive sampling with 2 respondents. Hypothesis testing was conducted using simple linear regression testing. The research results include: (1) Tourism facilities achieved in the good category (45.92%) and (2) Sense of satisfaction from visitors achieved in the good category (48.88%). The calculated F score is 104,186 and the significance is 0.000 <0.05, where the tourist facility variable has a big influence on visitors' sense of satisfaction, which is reviewed through the Adjust R Square value, namely 0.280. The tourist facilities variable contribution (X) to the visitor satisfaction variable (Y) reached 28% and 72% was influenced by other factors